P143 Implementation of an asymptomatic pathway significantly reduces clinic visit duration. (18th May 2015) - Cochrane, Sarah; Wheeler, Helen; Harryman, Lindsey
Abstract : Background/introduction: Our sexual health clinic in a busy city-centre is experiencing increasing patient demand. The challenge is to provide time-efficient, quality patient-care. Developing a structured screening pathway for asymptomatic patients to be seen by nursing assistants (NAs) could reduce time spent within clinic. Aim(s)/objectives: To successfully and safely introduce a pathway enabling NAs to screen asymptomatic, heterosexual patients. To assess the pathway's impact on patient-care including: Time spent within clinic Screening tests offered/accepted (following BASHH guidance) Methods: Baseline data was recorded for two weeks prior to pathway introduction. The asymptomatic pathway was implemented, including self-completed symptom questionnaire and patient assessment/testing tool. A competency package for NAs was introduced. Comparison of patient-care to baseline was made. Results: Eighty asymptomatic patients were identified during the initial two-week period. Following introduction, thirty-three patients followed the pathway. Four subsequently disclosed symptoms and were excluded. Discussion/conclusion: Early results show significant reductions in clinic visit duration. This improves patient experience, increases patient numbers and allows trained staff to manage complex patients. HIV test offer and uptake increased. More data are needed for future analyses. NAs will continue to be supported in pathway provision. Further elements will be introduced to assess and manage risk-taking behaviour.